PENGARUH SELF OF EFFICACY, PENGALAMAN KERJA DAN KOMPETENSI KERJA KARYAWAN TERHADAP PROMOSI JABATAN PADA BSI - Rindi Febriyani; Siti Halimahtusakdiah; Sandra Herliana Fadila; Maya Panorama (CV ODIS, 2022)
This research aims to determine the effect of each variable researched, namely the self of efficacy, work experience, and employee competence on the promotion of position. The population in this research is employees of Bank Syariah Indonesia. The type of research used in this research is quantitative research. The sample selection technique is done by random sampling with a sample of 50 people as respondents. Data collection techniques using a questionnaire and measurement using a Likert scale. Data analysis processing techniques used are multiple linear analysis and coefficient of determination analysis. The data is processed using SPSS 25. The results showed that self of efficacy, work experience, and employee competence the no significant effect on the promotion of the position of Bank Syariah Indonesia. The results of the R2 determination coefficient analysis showed that self of efficacy, work experience, and employee competence had an effect of 13.9% on the promotion of position, and the remaining 86.1% was influenced by other variables that were not studied.